Early polished stone tools in South China evidence of the transition from palaeolithic to neolithic - Zhao, Chaohong (Documenta Praehistorica, 2004)
The appearance of polished stone tools has been taken as one of the important indicators of the beginnings of the Neolithic. Early polished stone tools excavated in South China are discussed in this paper. The polishing technology developed from stone tools with polished blades to whole polished stone tools. Different kinds of polished stone tools appeared at different times. The earliest polished stone tools are axes, adyes and cutters, with only the blades polished. They date to 21000- 19000 cal BP. The whole polished stone tools appeared thousands of years later. The relationship of thepolishing technology with other factors during the transition from the Paleolithic to the Neolithic should be discussed after more detailed information has been obtained.
Keywords: arheološke najdbe; paleolitik; neolitik; kameno orodje; Kitajska